Pengaruh Pembelajaran Akuntansi Keuangan, Literasi Keuangan, dan Pendapatan Terhadap Perilaku Keuangan Mahasiswa Dalam Menghindari Pinjaman Online (PINJOL) - Deflena Deflena; Aditya Pradana; Haviz Taufik; Vera Amalia (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the influence of financial accounting learning, financial literacy, and income on students' financial behavior in avoiding online loans (pinjol). The background of this research is the rampant cases of online loans among students which have fatal consequences, such as the one involving IPB University students. This phenomenon highlights the need for a good understanding of personal financial management. The population in this study is the Accounting Study Program, Faculty of Economics and Business, Jambi University, totaling 453 students. Sampling used a purposive sampling technique with a total of 100 students. The data used is primary data obtained by distributing questionnaires directly (manually) to 100 respondents. The method used in this study is quantitative associative with a multiple linear regression analysis technique, and processed using SPSS version 22.0. The results of the study show that, partially, the financial accounting learning and income variables do not have a significant effect on students' financial behavior in avoiding online loans. However, the financial literacy variable has a positive and significant effect on students' financial behavior. This means that the higher the level of students' financial literacy, the better their financial behavior will be. Simultaneously, the three variables (financial accounting learning, financial literacy, and income) have a significant effect on students' financial behavior in avoiding online loans. This study concludes that financial literacy is the most important factor in shaping healthy financial behavior among students.